ECONOMIC GROWTH, REGIONAL STUDY IN SOUTHEAST ASIA DIGITAL MARKETING SECTOR - Mahendra, Prasetya Tri; Novaliana, Ika (FE Program Studi Manajemen, 2025)
This study aims to analyze the impact of the digital marketing sector on economic growth in the Southeast Asian region by using key indicators: broadband penetration and the number of people in the productive age group. These two variables are used to represent technological readiness and workforce capacity as drivers of digital-based economic growth.The research employs a quantitative approach with secondary data from ten Southeast Asian countries (Indonesia, Malaysia, Singapore, Thailand, the Philippines, Brunei Darussalam, Cambodia, Vietnam, Laos, and Myanmar) covering the period from 2019 to 2023. The analysis technique used is panel data regression with the Random Effect Model (REM) approach and assumption testing using the OLS method. The results show that the broadband variable has a positive and significant effect on economic growth, with a coefficient of 0.981 and a significance level of 0.000. This indicates that high-speed internet access is a crucial catalyst for the growth of the digital sector and economic activities in the region. The variable representing the productive agepopulation does not show a significant impact on economic growth, suggesting that the quantity of labor does not necessarily guarantee increased economic output unless accompanied by improvements in productivity and human capital quality.Keywords: Economic growth; digital marketing; Southeast Asia